Analisis Kinerja Keuangan PT Kalbe Farma Tbk Tahun 2021-2023 Berdasarkan Rasio-Rasio Keuangan - Ika Nurillah Ati; Mudji Kuswinarno (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to evaluate the financial performance of PT Kalbe Farma Tbk between 2021 and 2023 through the analysis of financial ratios, including liquidity, solvency, activity, and profitability ratios. The method used is a descriptive quantitative approach, utilizing secondary data from the company’s financial statements to conduct time series analysis. The study calculates and analyzes financial ratios to assess the company’s performance over the specified period. The results show significant changes in PT Kalbe Farma’s financial condition, with a notable increase in total assets and equity, although net profit experienced a significant decline in 2023. The liquidity ratios indicate that the company maintains strong financial stability and can meet its short-term obligations, while the solvency ratios reflect a prudent approach in debt management and a reduction in reliance on external financing sources. These findings highlight the importance of effective financial management in maintaining corporate stability amidst the challenges faced in the pharmaceutical sector